THE DESCRIPTION OF HANDS SHAKE AND VOICE TREMBLES IN CONDUCTING CLASS PRESENTATION BY THE 4TH SEMESTER STUDENTS AT PUTERA BATAM UNIVERSITY - Fasaaro Hulu (Universitas Putera Batam, 2018)
The purpose of this research is to identify the students’ hands shake and voice trambles in conducting presentation. The method used is qualitative describtive method. In data collection, researcher applied the closed quesionnaire through fifty students in three classes and to analyse the data by comparing and categorisation according to each its parts. And result displays in the form of text, table and chart. The result of this present research were found by the fifty students which were involved in the presentation. The first result were 33 students who got hands shake an there were 17 students who did not got hands shake in conducting presentation. the second, there were 34 students who got voice trembles and 16 students who did not got voice trembles in doing the class presentation. The most dominant faced by students in doing presentation is the voice trembles and the more dominant is the hands shake as found 16 students.